Optimasi Analisa Kadar ß Karoten Dalam Jagung (Zea mays.L) Dengan Metoda HPLC Terhadap Pengaruh Lama Perebusan, Variasi Eluen Dan Kolom - Endang Widaya Nengsih; Budhi Oktavia; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2013)
Corn contains a variety of important chemical compounds; one of them is vitamin A. Nowadays, a shortage of vitamin A becomes a problem for people in whole the world, especially for developing countries, including Indonesia. However, this problem can be reduced by increasing pro-vitamin A which is the precursor of vitamin A. The Pro-vitamin A is obtained from one of Indonesian staple food. It is corn. Unfortunately, the cooking process of corn can reduce the content of vitamin A precursors or β-carotene. The effect of boiling on β-carotene content can be analyzed by HPLC method, a UV-Vis detector at wavelength of 449 nm with C-8 column and an organic solvent of methanol 100%. Retention time for β-carotene is 6, 20 minutes. The effect of long boiling toward decreasing of β-carotene contents has been tested in this research. The result of β-carotene contents for long boiling in 20 minutes and 30 minutes after boiling process are 56, 02% and 68, 32%.